Effectiveness of Comic-Based Learning Media on Chemical Bonding Matter - Agussalim, Hastuti (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
This research is a research and development (Research and Development) that aims to produce a chemistry learning media product through comic visualization on chemical bonding material with a cooperative learning model of the NHT (Number Heads Together) type that is valid and effective. The development of learning media through comic visualization refers to the 4-D development model by Thiagarajan which includes the stages of defining, designing, developing and disseminating. This learning media has gone through a validation stage by validators/experts and has gone through limited trials, and has been revised by the developer to produce learning media that is valid, effective, and practical. The results of this study are: 1) assessment of the feasibility/validity of the media by 3 experts/validators in the very valid category; 2) at the limited trial stage to 21 students obtained an average learning outcome test score of 75 out of an ideal score of 100 with class completion of 81% or 17 people who completed. So the conclusion is that the learning media through comic visualization is valid after going through a feasibility test by the validator and effective after a limited trial was conducted on class X.3 students of SMAN 11 Pinrang.